Where Heaven and Earth Meet : Essays on Medieval Europe in Honor of Daniel F. Callahan. - Frassetto, Michael; Hosler, John D.; Gabriele, Matthew (Studies in the history of Christian traditions ;, 2014)
Where Heaven and Earth Meet is an interdisciplinary collection that focuses on the writings of Ademar of Chabannes, Western religious history and early Islamic Jerusalem.